Histamine and Organoleptic Quality of Raw Materials for Skipjack (Katsuwonus pelamis) Fresh Meat at PT. Samudra Perkasa Abadi Sibolga - Arwana, Defa; Hasanah, Uswatun; Thahir, Muhammad Agam (Universitas Teuku Umar, 2024)
One of the important economic commodities in North Sumatra Province is Tuna, Mackarel tuna and Skipjack tuna. Skipjack tuna (Kadsuwonus pelamis) is a type of fish that is easily damaged. The process of fish damage begins after catching until the product reaches consumers. The aim of this research is to evaluate raw materials at PT. Samudra Perkasa Abadi Sibolga for histamine and organoleptic parameters. The results obtained were that the spinal temperature of fresh skipjack tuna in May obtained an average value was -2.9 ◦C and in June an average value was -3.1 ◦C. The temperature values in these two months meet SNI 7788:2013. The histamine content in May obtained an average value of 9.6 ppm and in June an average value was 10.7 ppm. The histamine value in the second month of observation met the SNI 2729:2013 threshold. The organoleptic quality values from May to June obtained an average value of 8 for the parameters of eyes, gills, body surface mucus, smell and texture, while for the meat parameters a value of 9 was obtained. The results of the organoleptic values obtained were in accordance with the SNI 2729:2013 threshold. The results obtained show that the raw materials used are of very good quality